2013
DOI: 10.5560/zna.2012-0122
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and Hydrogen Isotopic Preference in Hydration Spheres of Magnesium and Calcium Ions

Abstract: Molecular orbital calculations were performed to estimate the 18 O/ 16 O and D/H isotopic reduced partition function ratios (rpfrs) of water molecules around magnesium and calcium ions. As model for water molecules in the ith hydration sphere of the cation in aqueous solutions containing that cation, we considered water molecules in the ith hydration sphere that were surrounded by water molecules in the (i+1)th hydration sphere in clusters, M 2+ (H 2 O) n (M = Mg or Ca; n up to 100). The calculations indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Thus, this suggests that the insufficient number of water molecules at ultrahigh concentration is responsible for the decrease in the hydration number of Ca ions. An earlier report suggested that the hydration number of the Ca ions in 1 m aqueous electrolyte is 9. ,, However, the hydration number at the ultrahigh concentration is much smaller than that in the dilute aqueous electrolyte …”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, this suggests that the insufficient number of water molecules at ultrahigh concentration is responsible for the decrease in the hydration number of Ca ions. An earlier report suggested that the hydration number of the Ca ions in 1 m aqueous electrolyte is 9. ,, However, the hydration number at the ultrahigh concentration is much smaller than that in the dilute aqueous electrolyte …”
Section: Resultsmentioning
confidence: 96%
“…An earlier report suggested that the hydration number of the Ca ions in 1 m aqueous electrolyte is 9. 15,25,26 However, the hydration number at the ultrahigh concentration is much smaller than that in the dilute aqueous electrolyte. 26 Furthermore, the peak at 737 cm −1 experienced a blue shift with the elevated concentration (Figure 3h).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies on aqueous electrolytes, it has been reported that calcium cations can have a hydration number of up to nine for the first shell if there are sufficient water molecules in the electrolyte, although there is some variation in this value depending on the analysis method. [29][30][31] Based on this, the discharge/charge tests were carried out in Ca-WP electrolytes with H 2 O/Ca 2+ molar ratios of more than or less than nine to clarify the effect of decreasing the hydration number of calcium ions.…”
Section: Resultsmentioning
confidence: 99%